What is misinformation and disinformation? Understanding multi-stakeholders' perspectives in the Asia Pacific. Issue 3 (3rd July 2022) - Gibbons, Andrew; Carson, Andrea
ABSTRACT: Misinformation and disinformation on digital platforms can cause serious harms by undermining the integrity of elections, destabilising political systems, and derailing public health messages. Yet, key decision-makers still struggle to agree on definitions of these terms. This dissensus can frustrate holistic approaches needed to tackle the harms caused by online falsehoods. This article focuses on the Asia Pacific and draws upon a comprehensive set of expert interviews in Singapore and Indonesia to investigate how digital platforms, civil society actors, academics, and journalists conceptualise misinformation and disinformation. We find existing definitions have been developed in 'information silos'. In response, we map stakeholders' key definitional indicators of misinformation and disinformation to identify overlap and difference and to explicate the role of harm in their conceptualisations. This framework is used to recast working definitions of misinformation and disinformation with the intention of assisting greater stakeholder collaboration needed to mitigate its societal harms.